Dynamic imaging of Ostwald ripening in copper oxide nanoparticles by atomic resolution transmission Electron microscope - Na Yeon Kim (Applied Microscopy, 2019)
Abstract Structural evolution of copper oxide nanoparticles is examined, especially with respect to Ostwald ripening under electron beam irradiation. Dissolution of the smaller particles into the larger one was clearly observed at the atomic scale using advanced transmission electron microscope.